The economic burden incurred by families caring for a young child with developmental disability in Uganda - Kenneth R. Katumba; Cally J. Tann; Emily L. Webb; Patrick Tenywa; Margaret Nampijja; Janet Seeley; Giulia Greco (PLOS Global Public Health, 2023)
Each year, nearly 30 million children globally are at risk of developmental difficulties and disability as a result of newborn health conditions, with the majority living in resource-constrained countries. This study estimates the annual cost to families related to caring for a young child with developmental disability in Uganda. Nested within a feasibility trial of early care and support for young children with developmental disabilities, this sub-study estimated the cost of illness, the cost of paternal abandonment of the caregiver and the affordability of care by household. Seventy-three caregivers took part in this sub-study. The average annual cost of illness to families was USD 949. The main cost drivers were the cost of seeking care and income lost due to loss of employment. Households caring for a child with a disability spent more than the national average household expenditure, and the annual cost of illness for all households was more than 100% of the national GDP per capita. In addition, 84% of caregivers faced economic consequences and resorted to wealth-reducing coping strategies. Families caring for a child with severe impairment incurred USD 358 more on average than those with mild or moderate impairment. Paternal abandonment was common (31%) with affected mothers losing an average of USD 430 in financial support. Caring for a young child with developmental disability was unaffordable to all the study households. Programmes of early care and support have the potential to reduce these financial impacts. National efforts to curb this catastrophic health expenditure are necessary.